Human Rights Violations and International Legal Responses - Ribut Harwanto, Edi (Politeknik Siber Cerdika Internasional, 2025)
Human rights violations remain a persistent global challenge, necessitating robust international legal responses to ensure accountability and justice. In recent years, conflicts, authoritarian regimes, and socio-political crises have intensified concerns over state and non-state actors committing systematic abuses. The study aims to examine contemporary human rights violations and assess the effectiveness of international legal mechanisms in addressing these issues. This research employs a qualitative approach, utilizing doctrinal legal analysis and case studies to evaluate the role of international courts, tribunals, and human rights organizations. It explores key legal instruments, such as the Universal Declaration of Human Rights, the Geneva Conventions, and the Rome Statute, in addressing war crimes, crimes against humanity, and genocide. The study also reviews reports from the United Nations, the International Criminal Court (ICC), and regional human rights bodies to assess enforcement challenges and gaps in international law. Findings reveal that while international legal frameworks provide essential mechanisms for addressing human rights violations, enforcement remains inconsistent due to political constraints, lack of jurisdictional authority, and non-cooperation by states. Case studies on Ukraine, Myanmar, Ethiopia, and Venezuela highlight the limitations and successes of legal interventions. The study concludes that strengthening international legal responses requires enhanced cooperation, judicial independence, and more effective sanction mechanisms. This research contributes to legal scholarship by critically analyzing enforcement gaps and proposing policy recommendations to improve global accountability in human rights protection.